Reconstructing the Paradigm of Religious Moderation Based on Maqāṣid al-Sharī‘ah and National Education Policy: A Juridical Pedagogical Analysis Towards Inclusive Education in Indonesia - Maltifal Maltifal; Yanfaunnas Yanfaunnas; Almawadi Almawadi; Nofrizal Nofrizal; Riki Saputra; Sukmareni Sukmareni (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Religious moderation has become a strategic agenda in Indonesia's educational development, serving as a response to rising social polarization, intolerance, religious extremism, and the challenges of diversity in the digital age. This study aims to reconstruct the paradigm of religious moderation by integrating maqāṣid al-sharī‘ah (the objectives of Islamic law) with national education policy from a juridico-pedagogical perspective, employing a qualitative approach based on a literature review. Data were gathered from contemporary Islamic legal literature, religious moderation policy documents, national education regulations, and studies on Islamic education and multiculturalism; these were analyzed using content analysis, comparative analysis, and conceptual synthesis. The research findings indicate that the fundamental values ​​of maqāṣid al-sharī‘ah namely the preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl) align with the goals of the national education system as outlined in Law Number 20 of 2003. The study proposes a new conceptual framework the Integrative Religious Moderation Paradigm which synergizes maqāṣid al-sharī‘ah principles, national values, character education, and inclusive education to address the challenges of a 21st-century multicultural society. These findings offer a theoretical contribution to the study of religious moderation and a practical contribution to the formulation of education policies that foster a more inclusive, tolerant, and civilized society in Indonesia